Teaching with digital media in writing studies an exploration of ethical responsibilities - Coley, Toby F., 1981- (Studies in composition and rhetoric, 2012)
Explores the ethical implications of using digital media tools in writing classroom, particularly first-year composition, but applied broadly as well. In this book, the author argues that in addition to Stuart Selber's three multiliteracies, teachers of writing must include ethical literacy when teaching students to compose using digital tools.